2018
DOI: 10.1002/nau.23863
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of the efficacy and safety of mirabegron and solifenacin monotherapy for overactive bladder

Abstract: Aim:We conducted a meta-analysis to evaluate the safety and efficacy of mirabegron (50 mg) and solifenacin (5 mg) monotherapy for overactive bladder (OAB) during a 12-week cycle. Methods: Randomized controlled trials (RCTs) of mirabegron and solifenacin for OAB were searched systematically by using MEDLINE, EMBASE, and the Cochrane Controlled Trials Register. The reference lists of retrieved studies were also perused. Results: Five RCTs which compared solifenacin with mirabegron were studied.Mirabegron achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 31 publications
(39 reference statements)
3
15
0
Order By: Relevance
“…The mean post-voiding residual volume was significantly higher in the solifenacin group. Similarly, dry mouth was higher in the solifenacin group, but the two groups did not differ significantly in terms of odd ratio for visual field abnormalities and constipation [13].…”
Section: Discussionmentioning
confidence: 80%
“…The mean post-voiding residual volume was significantly higher in the solifenacin group. Similarly, dry mouth was higher in the solifenacin group, but the two groups did not differ significantly in terms of odd ratio for visual field abnormalities and constipation [13].…”
Section: Discussionmentioning
confidence: 80%
“…In one study comparing the efficacy of solifenacin and mirabegron in patients who were not satisfied with treatment due to lack of efficacy among patients taking anticholinergics except solifenacin, efficacy with mirabegron 50 mg was similar to solifenacin 5 mg. 20 A recent meta-analysis comparing the effects of mirabegron and solifenacin showed that the therapeutic effect of mirabegron is similar to that of solifenacin. 28 Considering these evidence, OAB patients who experienced poor efficacy with previous anticholinergic treatment benefitted from mirabegron and solifenacin. Our study differed from that of the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…For meta-analysis, the study could be defined as a fixed-effects model if P > .05, if not, a random-effects model would be chosen. 1 However, in fig. 2(D), the heterogeneity test showed P = .51 and a fixed-effects model should be chosen instead of random-effects model.…”
Section: Re: Meta-analysis Of the Efficacy And Safety Of Mirabegron Amentioning
confidence: 97%